Keeping Our Eyes on the Eyes: The Case of Arcimboldo. (May 2014) - Bubic, Andreja; Susac, Ana; Palmovic, Marijan
While contemporaries often viewed his reversible composite heads as scherzi (jokes) and modern art connoisseurs as creative masterpieces, Giuseppe Arcimboldo's ingenious paintings served as inspiring stimuli for the present eye-tracking experiment. One group of participants viewed three chosen paintings in an upright, and another in an upside-down, orientation. We compared how participants viewed three selected areas of interest (AOIs) within the painting when these could, and could not, be identified as a face or distinct facial element (eyes and mouth). The obtained results indicate that the participants fixated the parts of the painting which represent faces more in the upright than in the inverted orientation. Furthermore, in the upright orientation the participants focused more on the upper AOIs (eyes) than the lower AOIs (mouth). This was not the case for the inverted orientation of two paintings. In conclusion, the face inversion effect occurs even in this artistic context, and the gaze often goes where the eyes are.